A Comparative Study of Two Game-Based Digital Platforms on Students’ Vocabulary Mastery in EFL Classrooms - Etik Umayah; Nirwanto Maruf (GLENS: Global English Insights Journal, 2026)
Vocabulary mastery is essential for EFL learners because it supports comprehension, communication, and classroom participation. However, many vocational students struggle when vocabulary instruction relies on memorization and teacher explanation. This study investigated the effectiveness of Wordwall and Baamboozle in improving students’ vocabulary mastery and compared which platform produced stronger learning gains. It employed a quantitative quasi-experimental pre-test–post-test non-equivalent group design. The participants were 86 tenth-grade students from two intact classes at a vocational high school in Gresik, Indonesia: 43 students learned through Wordwall and 43 through Baamboozle across six sessions on jobs and professions vocabulary. Data were collected using vocabulary pre-tests and post-tests and analyzed through descriptive statistics, paired sample t-tests, an independent sample t-test, and effect size analysis. The results showed that both groups improved significantly, p < .001. Wordwall scores increased from 61.25 to 76.48, while Baamboozle scores increased from 60.87 to 80.36. Baamboozle produced significantly greater gains, t(84) = -4.17, p < .001, with very large effects. This study is limited by its single-school sample, short treatment period, and one vocabulary topic. The findings imply that EFL teachers should select game-based platforms based on interaction, retrieval practice, and instructional fit.